Carotid artery distensibility and hormone therapy and menopause: the Los Angeles Atherosclerosis Study. Issue 2 (February 2016) - Shufelt, Chrisandra; Elboudwarej, Omeed; Johnson, B. Delia; Mehta, Puja; Bittner, Vera; Braunstein, Glenn; Berga, Sarah; Stanczyk, Frank; Dwyer, Kathleen; Merz, C. Noel Bairey
Abstract: Objective: Observational studies have suggested that arterial distensibility decreases during menopause; however, its relationship with hormone therapy use remains controversial. We prospectively studied distensibility and hormone therapy use at different menopause stages. Methods: One hundred sixty-one women (aged between 42 and 61 y) without cardiovascular disease underwent carotid artery measurements by ultrasound to calculate distensibility index at baseline and 3 years later. Menopause stage was classified at each visit as premenopausal, perimenopausal, and postmenopausal. Across 3 years of prospective observation, women were classified as remaining premenopausal, remaining postmenopausal, or transitioning (defined as change from premenopausal to perimenopausal, from premenopausal to postmenopausal, from perimenopausal to perimenopausal, or from perimenopausal to postmenopausal). Results: Distensibility declined across time at all menopause stages ( P < 0.0001). Compared with postmenopausal women, premenopausal and transitioning/no hormone therapy women had more than twice the decline in distensibility index ( P = 0.06 and P = 0.016, respectively), whereas transitioning/hormone therapy women did not differ in distensibility decline ( P = 0.28). In a multivariate model, change in systolic blood pressure ( P < 0.0001) and change in pulse pressure ( P = 0.004) were independent predictors of distensibility index change and served as effect modulators. In an adjusted model, women in the premenopausal and transitioning/no hormone therapy groups had a significantly faster decline in distensibility index ( P = 0.002 and P = 0.001, respectively) compared with postmenopausal women, whereas the transitioning/hormone therapy group did not ( P = 0.21). Conclusions: These findings confirm that the menopausal transition is associated with reduced vascular compliance. Hormone therapy is associated with better arterial distensibility only during the menopausal transition. Additional prospective studies are needed to confirm these findings and to determine whether hormone therapy use beyond the menopausal transition is related to distensibility.